Analysis of Disease Incidence in Yellow Curly Chili Plants (Capsicum fru-tescens L. ‘ORI 212’) Infected with Begomovirus in Kemudo, Prambanan, Klaten - Risma Khuril , Laili; Aprilia Sufi (BIOVALENTIA: Biological Research Journal, 2025)
Begomovirus is a genus of viruses that can affect chili plants, causing yellow curly leaf disease. The incidence of yellow curl disease in chili plants was first reported in Indonesia in 2000, and it has been increasing since then. Analyzing the occurrence of yellow curl disease is essential to determine the type of pathogen affecting chili plants and its impact on their growth, chlorophyll levels, and soil nutrients. This research aimed to analyze the incidence of yellow curl disease in the 'Ori 212' variety of chili plants (Capsicum frutescens L.) infected in Kemudo, Prambanan, Klaten. The presence of viral DNA was detected using SPG1 and SPG2 primers. The results revealed that out of 84 chili plants studied, 76 were infected with yellow curl disease, resulting in a disease incidence of 90% and a disease severity of 46%.Infected chili plants exhibited reduced growth, characterized by decreased plant height, leaf width, and leaf length. Additionally, the total chlorophyll levels in infected plants decree sed by 60% compared to healthy ones. Soil analysis indicated high levels of phosphorus (P), while nitrogen (N) and potassium (K) levels were l n conclusion, the research findings confirmed that the chili plants were positively infected with Begomovirus, as evidenced by the high incidence and severity of yellow curl disease, which adversely affected growth and chlorophyll levels. These results underscore the importance of developing sustainable agricultural strategies to mitigate the impact of viral diseases on crop productivity. Future research should explore effective management practices and resistant chili varieties to combat the effects of Begomovirus. .